Impact of Gender and Group Composition on Leadership in Small Groups - Chadha, Aastha (Tufts Archival Research Center, 2017)
Despite many advancements that have been made in the field of gender-equality, women continue to be underrepresented in the leadership positions in the workplace. This deprives companies of the talent and leadership skills that women bring to the table and also discourages women from pursuing these positions. The current study aims to examine two possible causes of this phenomenon: gendered stereotype threat and group composition. I examined the impact of gender and group composition on the frequency of leadership behaviors exhibited under the conditions of stereotype threat. A 2X2 between-subjects experiment was conducted to test this relationship. Gender was coded as male or female, and gender composition was manipulated by placing participants in in either gender-equal or female-majority groups. Leadership behaviors were measured on a scale adapted from one used by Lord (1975). Thirty-seven men and 59 women participated in 24 groups of four. The first hypothesis that men would display more leadership behaviors due to the negative impact of stereotype threat on women was not supported although data trended in the predicted direction. The second hypothesis that female-majority groups would overall display more leadership behaviors than the gender-equal group was largely supported. The last hypothesis that women in the female-majority groups would perform more leadership behaviors than women in gender-equal groups was not supported through the data trended in the predicted direction. The current study combines two usually distinct avenues of research and paves the way for future research into the ways stereotype threat can be mitigated by group composition.